Fatal Eastern Equine Encephalitis in a Patient on Maintenance Rituximab: A Case Report. (12th February 2017) - Solomon, Isaac H.; Ciarlini, Pedro D. S. C.; Santagata, Sandro; Ahmed, Asim A.; De Girolami, Umberto; Prasad, Sashank; Mukerji, Shibani S.
Abstract: A 63-year-old woman on rituximab maintenance for follicular lymphoma presented with headaches, vomiting, and fever, and was diagnosed with eastern equine encephalomyelitis by cerebrospinal fluid polymerase chain reaction. Eastern equine encephalomyelitis immunoglobulin (Ig)G/IgM remained negative due to rituximab treatment, and magnetic resonance imaging showed minimal abnormalities, making this a diagnostically challenging case. Despite therapy with intravenous Ig, the patient rapidly declined and died on hospital day 12. Autopsy revealed perivascular and parenchymal chronic inflammation, with an absence of B lymphocytes, and virally infected neurons throughout the central nervous system.